Puritanisme dan Perkembangan Pendidikan Amerika Masa Kolonial - Rusydi Muhammad Yusuf (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
This study aims to know the influence of puritanism in the early development of education in America, especially in the 1600s to the beginning of American independence. It is a qualitative research with a library or documentary design relies on the main data of ideas, views, or beliefs taken from sources in the form of books, texts and other documents related to America puritanism. The collected data are analyzed qualitatively using concepts and theories relevant to the problem being discussed. The research reveals American puritanism was a religious reform movement in the mid of 16th century aimed initially at purifying religious doctrines from the influence of Roman Catholicism. Although the puritans' thoughts had undergone ebb and flow, they still emerged nowadays in various activities, like in the president’s inauguration speech. America puritanism was sourced from individual freedom values that influenced their life pattern. American puritanism was not only a religious belief, but it was also a philosophy of life. American puritanism has had a great influence on American cultural values, and the formation of the character of the American nation. It had also a great influence on the development of education in America since colonial era. It can be concluded that the puritanism influence greatly on American education system from the beginning of the first immigrants who settled in the new world in 1600s. Penelitian ini bertujuan untuk menggali lebih dalam pengaruh puritanisme dalam pengembangan awal pendidikan di Amerika, khususnya pada 1600-an hingga awal kemerdekaan Amerika. Penelitian ini menggunakan metode penelitian kualitatif dengan rancangan penelitian yang berbentuk kajian kepustakaan. Data utama dalam penelitian ini gagasan, pandangan, atau keyakinan yang diambil dari sumber-sumber yang berbentuk buku-buku, naskah dan dokumen-dokumen lain yang berhubungan dengan puritanisme di Amerika. Data terkumpul dianalisis secara kualitatif dengan menggunakan konsep dan teori yang relevan dengan permasalahan yang sedang dibahas. Hasil penelitian memperlihatkan bahwa puritanisme Amerika adalah gerakan reformasi agama pada pertengahan abad ke-16, gerakan ini awalnya bertujuan untuk memurnikan doktrin agama dari pengaruh Katolik Roma. Walaupun hasil pemikiran kaum puritan selalu mengalami pasang surut, gagasan pemikiran mereka masih muncul dalam berbagai kegiatan, bahkan dalam pidato pelantikan presiden. Puritanisme di Amerika berpusat pada nilai-nilai kebebasan individu yang memiliki pengaruh terhadap pola kehidupan mereka. Puritanisme bukan hanya kepercayaan agama, tetapi juga filsafat kehidupan, kombinasi gaya hidup dan nilai-nilai. Berdasarkan temuan tersebut dapat disimpulkan bahwa doktrin puritanisme memberi pengaruh besar pada sistem pendidikan Amerika secara keseluruhan sejak awal imigran pertama yang menetap di dunia baru pada tahun 1600-an. تهدف هذه الدراسة إلى تحليل تأثير التزمتية في التطور المبكر للتعليم في أمريكا، و خاصة في القرن السابع عشر وحتى بداية الاستقلال الأمريكي. لقد أصبحت التزامية جزءًا من تاريخ الأمريكية، بل أصبحت أساسًا لتشكيل سلوك الأمريكي، على الرغم من أن نتائج أفكار المتشددين تواجه دائمًا صعودًا وهبوطًا، لكن أفكارهم الفكرية لا تزال تظهر في العديد من الأنشطة، حتى في خطاب تنصيب الرئيس. و تركز التزمتية في أمريكا على قيم الحرية الفردية، وقيمة التطهير لها تأثير على أنماط الحياة المتعلقة بالأفراد. الالتزمية ليست معتقدًا دينيًا فحسب، بل أيضًا فلسفة للحياة، مزيج من أسلوب الحياة والقيم. و كان للتزمتية تأثير كبير على القيم الثقافية الأمريكية، وتشكيل شخصية الأمة الأمريكية، وكان له تأثير كبير على تطوير التعليم في أمريكا منذ العصور الاستعمارية. و تستخدم هذه الدراسة أساليب البحث النوعي، وهي الأساليب التي تؤكد على جانب الفهم المتعمق للمشكلة من خلال دراسة كل حالة على حدة. و أظهرت النتائج أن المذهب التزمتي كان له تأثير عميق على نظام التعليم الأمريكي ككل منذ بداية المهاجرين الأوائل الذين استقروا في العالم الجديد في القرن السابع عشر.